Analysis of Foreign Ownership on Tax Avoidance - Isni Mardiani; Ombih Ajitama; Indra Pahala; Puji Wahono (CURRENT ADVANCED RESEARCH ON SHARIA FINANCE AND ECONOMIC WORLDWIDE, 2024)
Economic globalization has driven the flow of foreign direct investment (FDI) to various developing countries including Indonesia. Increasing foreign ownership in domestic companies has brought positive impacts such as job creation, technology transfer, and increased global competitiveness. However, on the other hand, there are concerns that foreign ownership in companies can also increase tax avoidance practices. Businesses with overseas ownership frequently exploit gaps in tax laws across different countries due to their access to global networks and additional resources. Research on a specific sample revealed that foreign ownership tends to have a detrimental impact on tax evasion. However, there are conflicting studies that suggest a positive or neutral outcome. This indicates that the level of tax evasion within a company is heavily influenced by its internal and external policies, as well as the various market environments it operates in.